Church Policy On Divorce, Coping Styles, And Psychosocial Well-Being Of Divorcees In Evangelical Churches In Nakuru, Kenya - Chebbet, Martha; Kamunyu, Ruth; Kiarie, Jane (IOSR Journal Of Humanities And Social Science (IOSR-JHSS), 2023)
Background: Incidences of divorce have become rampant among Christian couples. As a result, churches have come up with policies on divorce to guide how they respond to divorcees as a growing demographic group. However, some policies may make an already bad situation worse, necessitating effective coping styles. This study examined divorcee psychosocial well-being in light of Church policy on divorce in selected Evangelical Churches in Nakuru County. Specially, the study sought to establish the predominant policy adopted by evangelical churches in the county with a view to establish the implications on divorcee wellbeing. A secondary objective of the study was to determine the coping styles of divorcees in light of church policy on divorce and what it portends for the psychosocial wellbeing of divorcees in the church. Materials and Methods: A descriptive cross-sectional study design was used. The study was conducted among 121 divorcees in selected evangelical churches in Nakuru County in Kenya. Participants were recruited into the study through snowball sampling method. Data was collected using a structured questionnaire and analysed through descriptive statistical techniques in SPSS. Results: The lesser evil principle characterized the policy on divorce applied in Evangelical Churches in Nakuru County. Divorcees exhibited high spiritual wellbeing, followed by mental wellbeing, and lastly, social wellbeing. Their wellbeing was underpinned by spiritual coping styles. Conclusion: The lesser evil principle promotes psychosocial wellbeing of divorcees. Church leaders and members of congregation should be trained on how to respond to the problem of divorce in church in a manner that promote the wellbeing of divorce and draw them near to God.
Keywords: Church Policy on Divorce; Coping Styles; Psychosocial Wellbeing; Spiritual Coping